Integrated Mobility Hub Location Selection for Sustainable Urban Mobility - So, Jaehyun (Jason); Chae, Munhyun; Hong, Jiho; Youm, Juhyoun; Kim, Sang Hyun; Kim, Jinhee (Sustainable Cities and Society, 2023)
This study suggests a systematic approach for selecting the optimal locations for mobility hubs in urban areas, which serves as transfer centers for various modes of transport—including buses, metros, and emerging smart mobility services that operate underground, on the ground, and in low-altitude airspace. The emerging smart mobility services covered in this study include personal mobility, car sharing, demand-responsive transit, automated shuttles, and urban air mobility. This study establishes a two-step location selection approach: the first step uses vertiport obstacle analysis to exclude locations that could not support urban air mobility takeoff and landing requirements, and the second step employs an analytical hierarchy method to provide selection criteria and weights for the purpose of prioritization. The approach is applied for the selection of the location of mobility hub in Seoul Metropolitan Area. This two-step approach proposed in this study provides a practical method for selecting the location of a mobility hub where various mobility services with unique operational requirements exist, and ultimately it could be an excellent reference for urban mobility planners and engineers concerned with identifying and selecting the mobility-hub locations.
Keywords: Hub location; Location selection; Mobility hub; Mobility service; Optimal locations; Smart mobility; Transferability; Urban air; Urban air mobility; Urban mobility; Analytic hierarchy process; Mobility hub; Smart mobility; Transferability; Urban air mobility